The Effect of Infusion Breadfruit Leaves (Artocarpus Altilis (Parkinson) Fosberg) On Blood Glucose Levels in Male Mice (Mus Musculus) Diabetes Mellitus Type 2 - Simanjuntak, Helen Anjelina; Gurning, Kasta (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: The purpose of this study was to determine the content of secondary metabolite compounds contained in breadfruit leaf infusions which affect blood glucose levels and to determine the effective concentration of breadfruit leaf infusions which play a role in lowering blood glucose levels. Methods: The research method was carried out experimentally with the stages of making simplicia, making infusion, phytochemical screening and testing the breadfruit leaf infusion using the alloxan induction method. Antidiabetic testing was carried out in vivo on animal testing with 5 treatment groups (Na-CMC 1% w / v, Glibenclamide 0.65 mg / kg BW, breadfruit leaf infusion 300 mg / kg BW, 400 mg / kg BW, 500 mg / kg BW). Results: The results of phytochemical screening on breadfruit leaf infusion showed flavonoids, saponins and tannins. The results of the antidiabetic test with the alloxan induction method showed a decrease in blood glucose levels at the concentration of breadfruit leaf infusion 300 mg / kg BW, 400 mg / kg BW, 500 mg / kg BW. Conclusion: Breadfruit leaf infusion has an effect on reducing blood glucose levels in male type 2 diabetes mellitus mice.